Development and testing of a low-cost, dual-axis clinometer based on micro-electro-mechanical system sensors [electronic resource] - Yap, Yung Szen, 1983-; Rashdi Shah Ahmad; Amiruddin Shaari (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2007